Mechanical properties of soot particles : the impact of crosslinked polycyclic aromatic hydrocarbons - Pascazio, Laura (2021)
In this paper, we estimate the degree of crosslinking within soot particles making use of reactive molecular dynamics simulations of mechanical properties of crosslinked polycyclic aromatic hydrocarbons (PAH). Representative systems of PAH (pyrene, coronene, ovalene and circumpyrene) with a density similar to soot and with varying degrees of crosslinking were built. Uniaxial tensile test simulations were carried out on the systems and the yield stress of each sample was calculated. The hardness was estimated from the yield stress using an empirical conversion constant and the obtained values were compared with nanoindentation experiments of soot particles. The results show that mature ethylene and diesel soot particles are expected to present a degree of crosslinking between 2.1–3.0 and 3.0–3.5, respectively, to have a value comparable to the hardness found experimentally. Finally, an MD simulation of nanoindentation of a particle of crosslinked coronene molecules provided an alternative means to compute the empirical constant used to convert the yield stress in hardness. These results reveal the importance of crosslinking reactions during soot maturation that give rise to a structure in which the majority of aromatics are aliphatically linked in a 3D network.